Penggunaan Teknologi 3D Printing Dalam Pembuatan Clamp CNC Untuk Mendukung Praktikum CNC - Rizky Wirantara (Journal of Mechanical Engineering and Applied Technology, 2026)
CNC practicum activities in the Manufacturing Systems Laboratory require reliable clamping devices to ensure workpiece stability during machining processes. Conventional aluminum clamps present limitations in terms of weight, production cost, and maintenance. This study aims to design and evaluate the performance of a CNC clamp made from polylactic acid (PLA) using 3D printing technology. The research stages include three-dimensional modeling, slicing, printing with variations in infill density and nozzle temperature, mechanical testing through static loading, and economic analysis. The results indicate that a PLA clamp with 80% infill density can withstand a static load of up to 65 kg, meeting the requirements for light machining operations on wood and acrylic materials. Cost analysis demonstrates an efficiency improvement of up to 85% compared to conventional aluminum clamps. Therefore, the PLA-based clamp has strong potential as a lightweight, economical, and practical alternative to enhance the effectiveness of CNC practicum activities